Qualitative Analysis of Breastfeeding Practices among Lactating Mothers - Rodiawati Rodiawati; Vivi Silawati; Rukmaini Rukmaini (Indonesian Journal of Global Health Research, 2025)
Traditional postpartum care is still practiced in Cimanggu District. Based on 2024 data, 27 mothers experienced problems during the postpartum period caused by the use of bengkung, consumption of sambel peupeuh, application of campuh, and practicing the traditions of nyanda and sangsurkeun. Several factors influencing the practice of traditional care according to theories and previous studies include knowledge, attitude, culture, family support, and health worker support. Objective to analyze the factors influencing exclusive breastfeeding practices among mothers in Pancoran Mas District, Depok City, in 2025.  This research employed a qualitative approach to explore mothers’ experiences and perceptions of exclusive breastfeeding in Pancoran Mas District, Depok City. A total of 24 informants participated, consisting of 20 main informants (mothers with infants aged 6–12 months and family members) and 4 key informants (midwives and community health cadres). Participants were selected using purposive sampling. Data were collected through in-depth interviews guided by semi-structured interview protocols. All interviews were recorded, transcribed verbatim, and analyzed thematically using NVivo software to identify emerging themes related to perceptions, experiences, barriers, support systems, and workplace policies influencing exclusive breastfeeding. Trustworthiness of the findings was ensured through triangulation of sources, member checking, and peer debriefing. Most mothers perceived exclusive breastfeeding positively for maternal and infant health, yet concerns about physical changes, maternal fatigue, stress, cultural influences, and lack of workplace support emerged as barriers, while emotional, professional, and family support facilitated its practice. Exclusive breastfeeding is shaped by maternal perceptions, with support from family, health workers, and workplace policies playing a key role in sustaining the practice.